The Protection of Employee according to Taiwan Labour Standards Act - Lin, Geng-schenq (VNU Journal of Science: Legal Studies; Vol 34 No 2, 2018)
Established on July 30, 1984, the Taiwan Labour Standards Act (LSA)is the most important law that protects labourers in Taiwan. It was only after the LSA had been passed that the systematic researches on labour law actually began. As the LSA is a relativly new law, a number of its conceptionsare still vague; therefore, their application has caused certain difficulties. In this context, the Judiciary plays a decisive role. But, the common practice is that the judge frequently cites the scholars’ opinions to support his decision. This article explains how the judiciary cooperates with the scholars to give better answers, especially to protect the employee, through defining “employee”, “employee”, in relation to wages, working hours and dismissals. Overall, we agree with the famous German scholar Gallmmilscheg on his saying “Richterrecht bleibt unserer schicksal” (“Judiciary remains our destiny”) and the scholars will always make their contributions to this matter.  Keywords LSA, employee, employer, wage, working hours, dismissal. References   [1]    Y. H. Hou, The Review on the Legislation of the Norm of Labor Contract-Lessons from Japan, Taipei University Law Review 83 (2012) 211.   [2]    G. S. Lin, On the Subordination of the Employee, Labour Law Case Study(I), Hanlu Publisher, Taipei, 2002.   [3]    G. S. Lin, Zhenq Bou, On the Interpretation No. 740 of Judicial Yuan, Yue Dan Judiciary Times 60 (2017) 43.   [4]     G. S. Lin, From “de facto employment contract” to “failed employment contract”, Labour Law Case Study (II), Wu-Nan Culture, Taipei, 2009.   [5]    M. F. Ya, A Review on “the Same Employer” in Labor Standards Act, Taiwan Labor Quarterly 10 (2007) 32.   [6]    G. S. Lin, On the Concept of the Employer and the Extension of his Obligations , Labour Law Case Study (II), Wu-Nan Culture, Taipei, 2009.   [7]    Y. C. Lee, The Evolution and Trends of the Definition of Wages-Focus on Domestic Judicial Practice, Labor Law Journal 9 (2012) 1.   [8]    GDP: https://www.dgbas.gov.tw/point.asp?index=1 , https://www.stat.gov.tw/ct.asp?xItem=37407&CtNode=3564&mp=4 . Basic wages: https://www.mol.gov.tw/topic/3067/5990/13171/19154/ (2018/01/12).   [9]    S. H. Lee, The New Era ofWorking Hour Law in Taiwan, Taiwan Labor Quarterly 43 (2015) 18. [10]    G. S. Lin, The on Call Time - the Regulations in EU Countries, Labour Standards Act - 30 years after its implementation, Labour Ministry(Ed), 2014, 237-257. [11]    G.S.Lin, On the Working Hours, National Lawyer 14 4 (2010) 23.